Análisis mineralógico de la fracción arcilla de suelos tropicales del Perú por difractometría de rayos X y espectroscopia Mössbauer - Mejia, Mirian E. (2014)
The purpose of this work was to identify and to some extent characterize the main minerals in the clay fractions of soil samples from the Forest Reserve of the Universidad Agraria de la Selva, located in the Region of Huánuco, Peru, with emphasis on the iron oxides and iron-bearing clay minerals, using chemical dissolutive methods, such as dithionite-citrate-bicarbonate, DCB, [1] to dissolve preferentially crystalline iron oxides, and analytical techniques such as X ray diffractometry, XRD, and transmission Mössbauer spectroscopy, TMS, at room temperature, RT, and at 110 K was used to determine their mineralogical composition. This paper details the results obtained with two selected samples with contrasting characteristics.